(untitled) (Development Service Industry Management, 2024)
The article analyzes the issues of innovative technological activity and development of business entities, as well as financial support for these processes. It is shown that financial management acts, in fact, as a connecting link between innovative and technological activities of enterprises, investment and innovative management, as well as management of financial and economic aspects of business development, its optimization. It was established that the establishment of such an effective management system requires the formation of an appropriate information base, which is formed by relevant indicators. It was concluded that the development and testing of a directly balanced system of indicators is necessary to coordinate the relevant processes. Therefore, the purpose of the research is to develop a balanced system of criteria and indicators of financial management of innovative and technologically active enterprises. The benchmarks of innovative and technological business development and its financial support have been determined. It is pointed out that the restoration and further strengthening of the competitive positions of domestic enterprises requires the activation of their innovative and technological activities, which, in turn, relies on sufficient investment and financial support. It has been proven that both the possibilities of connection and the implementation of the functions and tasks of financial management in terms of managing the investment and innovation development of business entities require the development and application of appropriate regulatory and methodological support for internal use at enterprises. Such work is based on a balanced system of criteria, parameters and indicators. 5 vectors of business technology and their financial support have been determined: the sphere of production of innovative products; sector of sales of innovative products; aspects of technical and technological modernization of business; issues of general management; task of economic progress. A system of balance criteria has been determined between, on the one hand, changes occurring in the current production and economic activity of the enterprise (under the influence of the activation of innovative and technological activity) and, on the other hand, their consequences as a result of the creation of better prerequisites for the further activation of innovative and technological activity . The left side of the balanced indicator system is formed by the indicators of such components as production, economic efficiency, marketing, and the right side by finance, investment, innovative development.